Au-catalyzed lateral Ga(In)AsP nanostructures grown in a quasi-closed cell. (June 2022) - Vlasov, A.S.; Karlina, L.B.; Ber, B.Ya.; Bert, N.A.; Boiko, M.E.; Kazantsev, D.Y.; Levin, A.A.; Smirnov, A.B.; Smirnova, I.P.; Soshnikov, I.P.
Abstract: A new method for growth of Au-catalyzed lateral Ga(In)AsP nanostructures in a quasi-closed volume from a vapor source under semi-equilibrium conditions has been studied. Varied time-temperature conditions and nucleation modes were examined. It was found that lateral nanostructures elongated in the [ 1 1 ¯ 0 ] direction are formed on a (100) GaAs substrate at about 500 °C. Raising the growth temperature is accompanied by a significant change of the morphology of the nanostructures. The modified surface has a random textured structure with predominant pyramidal faceting. Changes in the alloy composition of the nanostructures were studied.